Unveiling Heat and Temperature Misconceptions: A Multilocation Study on First-Year College Students in Indonesia - Muliyani, Riski; Suhandi, Andi; Prima, Eka Cahya; Muslim, Muslim (Jurnal Ilmiah Pendidikan Fisika, 2024)
This study aims to identify misconceptions experienced by first-year university students regarding the concepts of temperature and heat. This research applied a descriptive research design. The sample consisted of 224 first-year students from public and private universities in Singkawang, Bima, Madiun, and the Sumedang, Sintang, and Bandung regencies. The instruments used were adopted from two previous studies and validated by experts. The test reliability results were 0.73 and 0.75, indicating a high level of reliability. Data were collected via Google Forms, using questionnaires and a four-tier test as the instruments. The findings indicated that the highest percentage of misconceptions among students occurred in the sub-topic “Temperature will continue to rise as long as the fire remains on while boiling water,” with 63% of students displaying this misconception. The lowest misconception occurred in the sub-topic “Water at 0°C has entirely turned into ice,” with 40.6% of students holding this misconception. It is hoped that these findings can be utilized by lecturers and teachers to address the sub-topics of temperature and heat, which are known to harbor numerous potential misconceptions. Consequently, lecturers can employ effective teaching strategies to address students’ misunderstandings regarding temperature and heat.